Hindu nationalism and media violence in news discourses in India. Issue 2 (2nd July 2020) - Falnikar, Ashwini
ABSTRACT: The mainstream media and communication discourses in India in the present times engender 'media violence' embedded in the dominant productions of 'Hinduism' together with aspirations for neoliberal development. The media violence engenders indigenous forms of racism and colonialism. This article attempts to examine the nature of these productions through critical theories of postcoloniality and decolonial approaches put into conversation with theories of journalism. Through the examination of the instances of selective silencing of journalistic voices, and erasures embedded within the journalistic practices, this article argues for critical theories of press freedom. The productions of racial superiority and internal colonialism in India only begin to make sense when read together with the interplays of religion, class, caste, and global reach of the privileged sections of Indian society, namely the civil society. Against the backdrop of the historical role of the press in India in freedom struggle against colonial rule, the history of press censorship after independence, the civil society voices that are amplified in the neoliberal restructuring of news media, and the Dalit movements that expose the Brahminical dominance in the imaginary of the 'Indian culture', the meanings of race and coloniality in India unfold.